2011
DOI: 10.1002/uog.10062
|View full text |Cite
|
Sign up to set email alerts
|

Four‐dimensional sonographic evaluation of avulsion of the levator ani according to delivery mode

Abstract: Objective To determine the frequency of avulsion of the levator ani muscle in primiparous women according to delivery mode, using introital four-dimensional ultrasonography. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 26 publications
(32 reference statements)
4
24
1
Order By: Relevance
“…The result is consistent with previously published data28-29, which reported an injury rate ranging from 13.3% to 38.5% after spontaneous vaginal delivery.…”
Section: Discussionsupporting
confidence: 93%
“…The result is consistent with previously published data28-29, which reported an injury rate ranging from 13.3% to 38.5% after spontaneous vaginal delivery.…”
Section: Discussionsupporting
confidence: 93%
“…The significance of age in our findings concurs with the results of some researchers [4]-[9]; however, other investigators did not find a significant difference associated with age in other studies focused on women who were primigravidas [7] [8] [11]. As shown in Table 1 , this may be due to sampling differences.…”
Section: Discussionsupporting
confidence: 92%
“…Chan [8] study- ing women in Hong Kong, reported mean age of 30.6 ± 3.9 years, which was similar to our sample, however they did not identify an association with LA injury in the bivariate analysis. In the Cassadó Garriga [11] study located in Spain, age was similar to our study, but the sampling reflected a case/control study, with cases selected on the basis of forceps delivery [11]. Their findings concur with others that forceps is an overwhelming factor in LA tear.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations